Endogenous Fluorescent Proteins in the Mucus of an Intertidal Polychaeta - Rodrigo, Ana P. (2022)
project LA/P/0140/2020 of the Associate Laboratory Institute for Health and Bioeconomy-i4HB. The National Mass Spectrometry Network (RNEM) under the contract POCI-01-0145-FEDER-402-022125 (ref.: ROTEIRO/0028/2013). Publisher Copyright: © 2022 by the authors. Licensee MDPI, Basel, Switzerland.